1997
DOI: 10.1159/000117396
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Artery Dissections

Abstract: Cervical artery dissection (CAD) accounts for up to one fifth of ischemic strokes occurring before 45 years. Their increasing recognition is probably due to an increased clinical awareness of this condition in patients with painful ischemic events. The internal carotid artery is the most commonly affected vessel. Cerebral ischemia is the most serious consequence of a CAD. It may be due to hemodynamic factors or emboli. The enlargement of the artery may lead to a direct compression of the lower cranial nerves. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
0
29

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(113 citation statements)
references
References 0 publications
4
80
0
29
Order By: Relevance
“…58,63 Treatment with Coumadin for 6 months-1 year has traditionally been advocated, with a target international normalized ratio of 2-3. 33,55 In a study on the treatment of blunt CA injury, anticoagulation was suggested to be the treatment of choice when dissection or pseudoaneurysm was diagnosed. 61 There are no data from controlled studies on the safety of heparin, although several consecutive series have shown no significant side effects.…”
Section: Management Optionsmentioning
confidence: 99%
“…58,63 Treatment with Coumadin for 6 months-1 year has traditionally been advocated, with a target international normalized ratio of 2-3. 33,55 In a study on the treatment of blunt CA injury, anticoagulation was suggested to be the treatment of choice when dissection or pseudoaneurysm was diagnosed. 61 There are no data from controlled studies on the safety of heparin, although several consecutive series have shown no significant side effects.…”
Section: Management Optionsmentioning
confidence: 99%
“…Most cases of ICA dissections present within hours; however, some develop over weeks as evolving symptoms leading patients to seek medical attention 17 . Symptoms of ICA dissection include headache, anterior neck pain, scalp tenderness, transient ischemic attack, cerebral infarction, amaurosis fugax, cranial nerve palsies, tinnitus and Horner's syndrome [18][19][20] . Sturzenegger et al 21 20 .…”
Section: Discussionmentioning
confidence: 99%
“…As the most common cause of stroke from dissection is thromboembolism, and because the risk of stroke seems to be greatest in the first day after the onset of the vascular injury, early anticoagulation has long been considered the first-line treatment [27][28][29][30][31]. However, only observational data exist and they are conflicting.…”
Section: Arterial Dissectionmentioning
confidence: 99%